The extracellular loop of Man-PTS subunit IID is responsible for the sensitivity of Lactococcus garvieae to garvicins A, B and C - Tymoszewska, Aleksandra (Sci Rep, 2018)
Mannose phosphotransferase system (Man-PTS) serves as a receptor for several bacteriocins in sensitive bacterial cells, namely subclass IIa bacteriocins (pediocin-like; pediocins) and subclass IId ones - lactococcin A (LcnA), lactococcin B (LcnB) and garvicin Q (GarQ). Here, to identify the receptor for three other narrow-spectrum subclass IId bacteriocins - garvicins A, B and C (GarA-C) Lactococcus garvieae mutants resistant to bacteriocins were generated and sequenced to look for mutations responsible for resistance. Spontaneous mutants had their whole genome sequenced while in mutants obtained by integration of pGhost9::ISS1 regions flanking the integration site were sequenced. For both types of mutants mutations were found in genes encoding Man-PTS components IIC and IID indicating that Man-PTS likely serves as the receptor for these bacteriocins as well. This was subsequently confirmed by deletion of the man-PTS operon in the bacteriocin-sensitive L. garvieae IBB3403, which resulted in resistant cells, and by heterologous expression of appropriate man-PTS genes in the resistant Lactococcus lactis strains, which resulted in sensitive cells. GarA, GarB, GarC and other Man-PTS-targeting bacteriocins differ in the amino acid sequence and activity spectrum, suggesting that they interact with the receptor through distinct binding patterns. Comparative analyses and genetic studies identified a previously unrecognized extracellular loop of Man-PTS subunit IID (γ+) implicated in the L. garvieae sensitivity to the bacteriocins studied here. Additionally, individual amino acids localized mostly in the sugar channel-forming transmembrane parts of subunit IIC or in the extracellular parts of IID likely involved in the interaction with each bacteriocin were specified. Finally, template-based 3D models of Man-PTS subunits IIC and IID were built to allow a deeper insight into the Man-PTS structure and functioning.